Cooperation of primary health care midwives with institutions taking care of women during their life span, newborns and neonates less than two months old - Biskupska, Maria; Niewiadomski, Tomasz Jarosław (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Primary healthcare (PHC) is based on a holistic concept of health that goes beyond the narrow medicalized model characterized by a high (sometimes too high) degree of specialization. It is recognized that the solution of various health problems requires a comprehensive approach. The examination of cooperation between different deliverers of healthcare to women and newborns of up to two months of age is a key step in the overall improvement of PHC. Aim of the study. The goal of this research was to make a preliminary evaluation of the cooperation between PHC midwives with other deliverers of healthcare to women and newborns. Results. Research was carried out in 2006 among midwives working in Poznań, Poland under contract with the National Sickness Fund. Thirty-eight of the 46 midwives who received anonymous surveys returned the forms and 29 correctly filled out forms were analyzed. Only these questions concerning cooperation between PHC midwives and institutions acting on the behalf of women, newborns and infants are considered here. Conclusions. Primary healthcare physicians, nurses and gynecologist obstetricians are the healthcare providers indicated as those who PHC midwives most often work with and the quality of cooperation is most often evaluated as very high or high. Often a lack of cooperation between PHC midwives and long term care nurses (16) and school nurses (11) is indicated, which requires further observation and evaluation.